Hormonal induction maturation of silver pompano Trachinotus blochii - Putra, Wiwin Kusuma Atmaja; Raza’i, Tengku Said (Jurnal Akuakultur Indonesia, 2020)
ABSTRACT This study was aimed to acquire the most suitable hormone treatment to induce gonad maturation of silver pompano Trachinotus blochii. This study used a completely randomized design with four treatments and three replications, i.e NaCl 90% (control) (0.5 mL/kg), hCG (20 IU/kg fish body weight), PMSG (20 IU/kg fish body weight), and PG600 (20 IU/kg fish body weight). Parameters measured were gonadosomatic index (GSI), hepatosomatic index (HSI), gonad maturity level (TKG), gonad histology, and absolute growth. The best result was PG600 treatment with 0.12% gonadosomatic index, 2.29% hepatosomatic index, TKG IV, and 85 g absolute growth for four weeks. This study concludes that the most suitable hormone to induce gonad maturation of silver pompano Trachinotus blochii is PG600 with 20 IU/kg body weight, which effectively affects GSI, HSI, and absolute growth of silver pompano. Keywords: hCG, maturation, PG600, PMSG, silver pompano. ABSTRAK Penelitian ini bertujuan untuk mendapatkan hormon yang terbaik untuk menginduksi maturasi gonadikan bawal bintang. Hormon yang digunakan pada penelitian ini adalahkontrol NaCl 90% (dosis 0,5 mL/kg), hCG(dosis 20 IU/kg bobot tubuh ikan), PMSG (dosis 20 IU/kg bobot tubuh ikan), dan PG600 (dosis 20 IU/kg bobot tubuh ikan). Parameter yang diamati adalah indeks gonadosomatik (GSI), indeks hepatosomatik (HSI), tingkat kematangan gonad (TKG), histologi gonad, dan pertumbuhan bobot mutlak. Hasil terbaik adalah perlakuan PG600 dengan gonadosomatik indeks (0,12%), hepatosomatik indeks (2,29%), TKG IV,dan pertumbuhan mutlak (85 g) selama empat minggu. Kesimpulan penelitian ini adalah perlakuan hormone yang berpotensi menginduksi maturasi gonad ikan bawal bintang adalah hormon PG600 dengan dosis 20 IU/kg bobot tubuh dikarenakan adanya pengaruh nyata tehadap parameter GSI, HSI dan pertumbuhan mutlak ikan bawal bintang. Kata kunci: ikan bawal bintang, hCG, PMSG, PG600, maturasi.